Risk and Reward in Managua's Commercial Sex Market: The Importance of Workplace - Willman, Alys (2012)
This article focuses on the capabilities of women in sex work--a sector in which a substantial number of women in developing countries find themselves. Sex workers confront important unfreedoms-violence and disease--on a daily basis. How well sex workers can manage these threats has implications not only for the workers themselves but also their families and communities, and thus is an important concern in development policy. Using original data from Managua, Nicaragua, I show how workplace conditions determine women's autonomy to manage risks of disease and violence, including their capacity to negotiate appropriate risk compensation. I present a model of a segmented labor market, and describe how women's autonomy in choosing a particular segment is constrained by access to networks and human capital. Next, I estimate the compensation to different risks by market segment. I find that sex workers in higher-end segments are less likely than women in other segments to take risks to their health or safety, and more able to charge a high-risk premium when they do. In addition, women who enjoy more autonomy in decision-making take risks less often than those whose decisions are constrained either by a manager or by low earnings. These findings indicate the need to consider differences in workplace conditions in designing policy to expand the capabilities of women in sex work.